Russell's Multiplicative Axiom - Lewandowska, Katarzyna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2012)
We present the history of two parallel (and equivalent) discoveries: the axiom of choice and the multiplicative axiom. Firstly, we consider the origins of the formulation of the multiplicative axiom. Next, we concentrate on Russell’s attitude towards the role of this axiom, which is closely related to his philosophy of mathematics. We also highlight some diﬀerences between Russell’s and Zermelo’s propositions.